Research on Nonlinear Bearing Characteristics of Conical Deformation Friction Pairs in the Hydro-viscous Cluth Considering the Influence of Structural Parameters - Sun Hao; Cui Hongwei; Mei Bizhou; Li Donghui; Suo Yiran; Zhang Lingqing (Jixie chuandong)
In purpose of getting the influence of different structural parameters on the bearing characteristics of the conical deformation friction pair, the equivalent contact model of the conical deformation friction pair under different structural parameters is established. The buckling deformation simulation is carried out by Ansys Workbench, and combined with the analysis of the Matlab numerical model, the variation law of the oil film thickness of the friction pair under different structural parameters is obtained. Based on the oil film pressure and micro-convex peak rough contact model, the variation law of the maximum total contact pressure during 10 s soft start is found, and the method of selecting the optimal structural parameters of the friction pair under the actual operating conditions is summarized. The results show that the axial deformation and the increase of the thickness of the steel sheet can make the deformation of the middle diameter of the steel sheet more difficult, and lead to the increase of the maximum total contact pressure of the friction pair. At the same time, it leads to non-uniform contact and non-uniform distribution of contact pressure, and different ratios of inner diameter to outer diameter can only affect the distribution location of the maximum total contact pressure of the friction pair, without having any great influence on its variation law and value. The research results provide a basis for the study of torque characteristics of conical deformation friction pairs under different structural parameters.